Recommendation of precision medicine application in Indonesia from multiple perspective: a review - Urfa Khairatun Hisan; Muhammad Miftahul Amri (Intelektual Pustaka Media Utama, 2023)
Recently, precision medicine has gained much attention. Precision medicine helps reduce trial-and-error prescribing and minimize adverse drug reactions while improving the drug's effectiveness. Precision medicine is a medical method that seeks to maximize healthcare quality by tailoring the healthcare process to each patient's unique characteristics. In the era of rapid technological growth and data explosion, precision medicine's development has become very promising. Development of techniques for obtaining medical data; significant reductions in the cost of bio sequencing; massive development of computing tools, storage systems, and wireless communication systems; as well as the development of data analysis techniques based on artificial intelligence have all become significant driving forces in the advancement of precision medicine. In this manuscript, we summarized previous studies on precision medicine development. In addition, we discussed the opportunities and potential challenges of precision medicine development, particularly in Indonesia. Despite its promising potential, many challenges remain to be overcome to develop precision medicine. Good regulations for patient data ownership and clinical data-sharing, followed by sufficient data infrastructure and human resource capabilities, are the most critical factors in ensuring success in precision medicine. Moreover, guaranteeing data safety, patient privacy, and genome fairness are other issues that must be addressed.